The blue door: A portal to a community of learners. Issue 1 (2nd January 2023) - Miller, Travis
ABSTRACT: For Terry Wood, the personal and professional were seamlessly connected. In her "House with the Blue Door" graduate students and visiting scholars lived; people gathered for conversations and music; the community reflected and found connections between important ideas. This chapter sets the stage for the special issue by contextualizing Terry's personal and professional life with anecdotes shared during the May 2021 Terry Wood Memorial Event. We see how she conceptualized knowledge development as a collective enterprise, putting into practice this worldview as a basis for life and for advancing the field of mathematics education. This reflexive relationship between theory and practice informed a body of powerful scholarship that continues to shape the field. Less recognized—and perhaps more importantly—these stories, and the subsequent chapters, reveal how Terry's investment in teachers, graduate students and colleagues resulted in the growth and development of scholars and teachers across multiple countries and continents.